Two-dimensional assessment of submillimeter cancer-free margin area in colorectal liver metastases. Issue 27 (July 2016) - Takamoto, Takeshi; Sugawara, Yasuhiko; Hashimoto, Takuya; Shimada, Kei; Inoue, Kazuto; Maruyama, Yoshikazu; Makuuchi, Masatoshi
Abstract : Abstract: The aim of the study is to evaluate the prognostic impact of the extent of submillimeter or zero surgical margin (SubMM) area among the patients who underwent liver resection for colorectal liver metastases (CRLM). The influence of suboptimal margin width of <1 mm on long-term outcome is unclear. A total of 423 liver resections for CRLM were performed at Japanese Red Cross Medical Center between 2007 and 2015. Among them, we identified 235 patients who underwent curative initial liver resection and classified them into 2 groups: R0 (margin: ≥1 mm) and R1 (SubMM). The R1 group was further divided into 2 groups by the extent of SubMM area: small SubMM area (⩽4 cm 2 ) and broad SubMM area (>4 cm 2 ). The median tumor number was 4 (range 1–97), 23% had solitary and 37% had 8 or more number of metastases. With a median follow-up period of 30 months, the overall 1-, 3-, 5-year survival for R0 (n = 72) versus R1 (n = 163) groups were 98.4% vs 87.5%, 75.5% versus 57.1%, and 50.1% versus 36.6%, respectively ( P = 0.004). After propensity score analysis allowing for matching the tumor number (<8 vs 8 or more), tumor size, and serum carcinoembryonic antigen level, the DFS and OS were significantly higher in the small SubMM area group ( P = 0.024, P = 0.049), respectively. Although wide margins >1 mm should be attempted whenever possible, reducing the extent of SubMM area (⩽4 cm 2 ) can contribute to better long-term outcome when wide margin is not practicable.